Membudayakan Literasi Anak Melalui Pendirian Ruang Baca Nusantara Desa Sukorejo Kecamatan Kotanyaar Kab. Probolinggo - Nabila, Halimatun (ELEMENTARY : Journal of Primary Education, 2023)
This pandemic period has resulted in education being less effective because every school is not allowed to carry out face-to-face learning, so students or college students must study online, from early childhood education to higher education. Therefore, the UNZAH PKM KKN group took the initiative to establish a reading room to reduce the use of gadgets and make children accustomed to reading books and reduce the use of gadgets and the misuse of social media.